2016
DOI: 10.1039/c6ta06022f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine nickel–cobalt alloy nanoparticles incorporated into three-dimensional porous graphitic carbon as an electrode material for supercapacitors

Abstract: A facile method was developed to synthesize ultrafine Ni–Co alloy nanoparticles embedded into 3D porous graphitic carbon, an excellent electrode material for supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…. sufficient space for electrolyte transport during charge/ discharge process. Furthermore, the intimate interaction between the graphitic carbon and Co 9 S 8 nanoparticles enables sufficient electron transport to the redox active sites [82][83][84][85]. After 5,000 cycles, the capacitance retention of Co 9 S 8 @SNCC was 98%, demonstrating excellent cyclic stability.…”
Section: Mofs In Combination With Other Materials As Carbon Sourcesmentioning
confidence: 76%
“…. sufficient space for electrolyte transport during charge/ discharge process. Furthermore, the intimate interaction between the graphitic carbon and Co 9 S 8 nanoparticles enables sufficient electron transport to the redox active sites [82][83][84][85]. After 5,000 cycles, the capacitance retention of Co 9 S 8 @SNCC was 98%, demonstrating excellent cyclic stability.…”
Section: Mofs In Combination With Other Materials As Carbon Sourcesmentioning
confidence: 76%
“…However, their capacitances are relatively low due to the inherent limitation of the electrostatic surface charging mechanism. In contrast, the specific capacitance of pseudocapacitors is much higher than that of EDLCs as electrode materials of pseudocapacitors (including conducting polymers [10][11][12] , transition metal oxides [13][14][15][16] and their relative composites [17][18][19] ), which hold higher theoretical capacity owing to fast and reversible faradaic reactions at the electrode/electrolyte interface, affording optimum supercapacitive properties than carbon-based materials [20,21] . Therefore, advanced pseudocapacitive materials based on transition-metal oxides/hydroxides have been receiving wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal alloy materials such CoNi alloy nanoparticles have exhibited great potential as electrode materials for high performance supercapacitors in alkaline electrolyte. 19,20 These reported studies demonstrated that CoNi alloy nanoparticles can not only provide more electrochemical active sites created by their oxides/oxyhydroxides generated on the surface of CoNi alloy nanoparticles through electrochemical activation in alkaline electrolyte, but also significantly improve electrode material's conductivity owing to the role of CoNi alloy particles as electron collector, thus improving the performance of supercapacitor. 16 A recent study on Ni-Co double hydroxides has discovered that Ni-rich active species ensure higher capacitance, while Co-rich species contribute better rate performance and long cycle life due to their higher electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of Co/Ni-based active components into porous carbon structures has been widely adopted to fabricate high performance electrode materials for supercapacitors. 18,19,[22][23][24][25] The advantages of the above approach mentioned are: (1) the formed carbon material concurrently as reduction reagent to in situ reduce Co 2+ /Ni 2+ on carbon structure into metal Co or Ni or CoNi alloy nanoparticles; (2) carbon material with high surface area capable of improving the dispersibility of Co or Ni or CoNi alloy nanoparticles, favourable for the exposure of electrochemical active sites; (3) the formed Co or Ni or CoNi alloy nanoparticles on carbon substrate with enhanced electrical conductivity, favourable for electron transfer; (4) the composite with porous structure to improve redox-related mass transport during electrochemical measurement. These advantages of the fabricated composites collectively contribute high supercapacitor performance when used as electrode materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation